Evaluation the drift using tips of pulverization with backpack manual sprayer in coffee tree - Miranda, Gustavo Rabelo Botrel; Silva, Marcos dos Reis; Alves, Alberto Donizete; Gonçalves, Eugenio José (Coffee Science - ISSN 1984-3909, 2016)
The efficiency of foliar application of certain products on the coffee depends on the majority of cases, the coverage of the leaf surface with the product applied in spray form. This study aimed to quantify the deposit of liquid applied on coffee leaves and stems occurred when applied using a backpack sprayer, equipped with conical nozzles with different spray nozzle. The experimental design was the randomized block design (DBC) in a split-plot for the evaluation of drift, with five treatments (JD-10 known as “flat iron”; J4-2; J5-2; J6-2 and JA-2) with four replicates in both designs. To quantitatively evaluate the spray coverage the drift, was prepared a solution composed of the tracer brilliant blue food coloring coloring (FD & C Nº. 1) 0,15% (p /v) and sprayed over the coffee tree. To assess the amount of drift was used Petri dishes, which were distributed in the following points: the first plaque in the center of the plant the second plaque in the projection of the coffee tree and the third plate of 0.40 m projection of the coffee bar. The results showed that the tips JD-10, J4-2 and JA-2 were the ones that showed the best results providing lower losses during spraying.